"Text transformation and freewriting methods as determinants of achievement in Yoruba essay writing in senior secondary schools in Ibadan, Oyo state " (2014)
The objective of this study is to determine which of the two teaching strategies: text transformation and free writing could better enhance students’ achievement in Yoruba essay writing. A pretest, posttest, control group quasi experimental design with 3 * 2 * 2 factorial matrix was adopted for the study. A multi-stage sampling procedure was used to select respondent in Ibadan north local government area in Ibadan metropolis. Forty students were randomly selected among the SS 2 students in the 3 selected schools. This study has 120 participants in all. Each of the schools was assigned to treatment at random. Data were collected using main instruments: Yoruba essay writing achievement test (YEWAT) and operational guide for instruction in text transformation, free writing and modified lecture methods, (OGITT, OGIFW, OGIMLM). One hypothesis, tested at 0.05 level o f significance was formulated for this study. Data were analyzed using analysis of covariance and scheffe post hoc. The findings revealed that there was a significant main effect of treatment on students’ achievement in Yoruba essay writing (/(2,109) = 76.205; p < 0.05). Scheffe post hoc analysis shows that the test transformation method (tt) has the highest mean score of (398.025), free writing (FW) with higher mean score of (388.401) lecture method with high mean score of (319.001). The findings from the study show that text transformation method had a significant impact on students’ writing achievement than other methods. It is recommended that teachers should affect the use of text transformation method in the teaching of Yoruba essay writing in the senior secondary schools while free writing should be used as pre-writing skill to generate content knowledge. Also teachers should use relevant and familiar instructional materials to teach subject matters while parents and students should cultivate positive attitude to Yoruba language as a school subject to protect and preserve our cultural heritage and develop our society morally, socially and technologically.